2006
DOI: 10.1128/mcb.00135-06
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin L Stabilizes the Histone Modification Landscape on the Y Chromosome and Pericentromeric Heterochromatin

Abstract: Posttranslational histone modifications and histone variants form a unique epigenetic landscape on mammalian chromosomes where the principal epigenetic heterochromatin markers, trimethylated histone H3(K9) and the histone H2A.Z, are inversely localized in relation to each other. Trimethylated H3(K9) marks pericentromeric constitutive heterochromatin and the male Y chromosome, while H2A.Z is dramatically reduced at these chromosomal locations. Inactivation of a lysosomal and nuclear protease, cathepsin L, cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 67 publications
4
38
1
Order By: Relevance
“…We generated two Flp-In TM -3T3 cell lines stably expressing either H2A or H2A.Z tagged with the SNAP epitope. Consistent with previous observations (Bulynko et al, 2006;Dryhurst et al, 2009;Greaves et al, 2007;Rangasamy et al, 2004), both variants showed a similar nuclear distribution and neither accumulated at the PHC at steady-state levels in our model system (supplementary material Fig. S1A,B).…”
Section: Different Dynamics Of H2a and H2az Deposition At Phcsupporting
confidence: 92%
See 1 more Smart Citation
“…We generated two Flp-In TM -3T3 cell lines stably expressing either H2A or H2A.Z tagged with the SNAP epitope. Consistent with previous observations (Bulynko et al, 2006;Dryhurst et al, 2009;Greaves et al, 2007;Rangasamy et al, 2004), both variants showed a similar nuclear distribution and neither accumulated at the PHC at steady-state levels in our model system (supplementary material Fig. S1A,B).…”
Section: Different Dynamics Of H2a and H2az Deposition At Phcsupporting
confidence: 92%
“…Therefore, we wanted to determine whether the perturbations in new H2A.Z deposition observed in cells with altered PHC translated into alterations in the steady-state distribution of total H2A.Z. By antibody staining in cells with an unaltered PHC state, both H2A variants displayed similar localization, with even distribution at euchromatin and heterochromatin, consistent with previous observations (Bulynko et al, 2006;Greaves et al, 2007;Rangasamy et al, 2004) (Fig. 5A,B).…”
Section: Different Dynamics Of H2a and H2az Deposition At Phcsupporting
confidence: 82%
“…A null mutant of ctsb in the mouse is homozygous viable but exhibits significantly increased amyloid plaque formation in a mouse model for Alzheimer's disease. In addition, cathepsins have been found in the nucleus and can proteolytically cleave histones to modulate chromatin and regulate ES cell differentiation (Bulynko et al, 2006;Duncan et al, 2008), as well as regulate the CUX1 transcription factor (Ceru et al, 2010;Goulet et al, 2004). Thus, Ctsba could modulate, through proteolytic cleavage, the activity of transcription factors, chromatin or other factors acting in dorsoventral patterning or morphogenesis.…”
Section: Discussion Ctsba Endopeptidase Function In Developmentmentioning
confidence: 99%
“…An increasing number of functionally important cytosolic or nuclear proteins are assigned as substrates for the lysosomal protease cathepsin L 7,22,29,30 . However, the biogenesis of bona fide cytosolic or nuclear cathepsin L is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to cleave the CDP/Cux transcription factor thereby driving G1/S transition of the cell cycle and by cleavage of 53BP1 cathepsin L might contribute to genomic instability in triple-negative breast cancer cells 7,27,28 . Nuclear cathepsin L seems to influence histone modifications, since epigenetic marks on the Y chromosome are reorganized in cathepsin L-deficient mouse fibroblasts 29 . Furthermore, recent reports demonstrated cleavage of the N-terminal tail of histone H3 by cathepsin L during embryonic stem (ES) cell differentiation 30,31 .…”
mentioning
confidence: 99%